The human condition in the digital age - Abrudan, Elena (Journal for the study of religions and ideologies, 2024)
Review of Sandu Frunză's volume Căutarea autenticității în era digitală. Eseuri despre poezie, filosofie și spiritualitate (Searching the Authenticity in Digital Era. Essays on Poetry, Philosophy and Spirituality) (București: Eikon, 2023).